NIR-light-mediated spatially selective triggering of anti-tumor immunity via upconversion nanoparticle-based immunodevices - Hongqian Chu (Nature Portfolio, 2019)
The use of immunotherapy can be limited by adverse side effects. In this study, the authors designed a nanodevice that spatiotemporally controlled activate immunomodulatory agents at the tumour site upon near-infrared light triggering, thus preventing systemic toxicity with maintained efficacy